Effects of basaltic rock powder added in substrates for Pinus elliottii seedlings (Revista de Ciências Agroveterinárias, 2015)
Even with commercial substrates for forest seedlings available in the market, new mixtures of components, potentially adequate for its physical and minerals characteristics, continue to be studied. The rock crushing powders, sometimes discarded at the end of the process, can be used in the composition of substrates, since it does not pollute and it gives some benefits for plants. This study aimed to evaluate the effects of basaltic rock dust mixed in different percentages with peat-based compost commercial and expanded vermiculite, in seedling production of Pinus elliottii. Five treatments (formulations) were evaluated regarding on the aerial height, the stem diameter and the ratio between aerial part height and stem diameter of seedlings produced by seeds in plastic tubes, as well as its survival after 180 days. In the overall context, the substrate with 10% of basalt powder added to 10% of vermiculite + 80% of commercial compost with peat was the most efficient for seedling development. The seedling survival was not affected by basalt powder.
Keywords: Residue; Basalt; Powder; Substrate; Pinus elliottii.